The effectiveness of mind map treatments on writing accuracy at Islamic Higher Education - Aisyah Hafshah Saffura El-Muslimah; Rudi Hartono; Abdurrahman Faridi; Puji Astuti (Universitas Negeri Semarang, 2021)
The study attempted to investigate the learners’ writing accuracy amongst digital mind map, paper mind map, and non-mind map treatments. There were two variables: types of mind map having three variances: digital mind map (x1), paper mind map (x2) and non-mind map (x3) as independent variable and writing accuracy (y) as the outcome variable. The study involved L2 participants at higher education in Kalimantan consisting of three groups based on types of mind map: digital mind map/x1 (n=24), paper mind map/x2 (n=23), non-mind map/x3 (n=23).The total number of the participants was 70 students, consisting two groups: experiment 1, (digital mind map class), experiment 2, (paper mind map class), and a control class (non-mind map class). A one way Anova was used to measure an effect of types of mind map on learners’ writing score. The finding confirmed that there was a significant effect of types of mind maps at the p<.05 level for the three different treatments [F (2, 67) = 5.811, p = 0.005]. Post hoc with Tukey HSD test confirmed that the average score for digital mind map (M = 76.79, SD = 9.76) differed significantly than paper mind map (M= 68.78, SD 12.32) at p=0.050 and non-mind map at p=0.005. However, paper mind map did not differ significantly than non-mind map ((M= 65.83, SD 12.12) at p= 0 .657. The further studies with larger sample size were needed to validate the research findings. Abstracts max 200 words.